Structural, optical and magnetic behavior of Sn doped ZnO nanoparticles prepared by solid state method. (2022) - Johnson Jeyakumar, S.; Vasudevan, J.; Arunkumar, B.; Jothibas, M.; Rajeswari, A.; Sathiskumar, R.; Muthuvel, A.
Abstract: The present work synthesis pure and Sn doped ZnO-NPs by solid state reaction method is reported to develop ZnO-NPs for magnetic application. The synthesized nanoaprticles were characterized by structural (X-ray), optical (UV–Vis), morphological (SEM with EDAX), functional group analysis (FT-IR) and PL spectroscopy. The X-ray diffraction analysis of Sn doped ZnO-NPs confirmed hexagonal wurtzite strcture of ZnO with minimum crystal size about 32.7 nm. UV–visible analysis shows that the Sn concentrations increased the amount of the catalyst and the formation of defects increased. The SEM study reveals the surface and ultra structure morphology of synthesized nanoparticles. To examine the various functional groups FT-IR was utilized. Due to annealing effect, Sn doped ZnO-NPs shows higher saturation magnetization at room temperature.